Effect of somatic cells co-culture on cleavage and development of in-vitro fertilized caprine embryos - KHARCHE, S D; GOEL, A K; JINDAL, S K; SINHA, N K; YADAV, P (The Indian Journal of Animal Sciences, 2011)
The present investigation was undertaken to study the influence of granulose cell monolayer and oviduct epithelial cell co-culture on developmental competence of in-vitro fertilized goat oocytes. Ovaries (1050) were collected from local abattoir and transported within 4h to the laboratory in warm saline (37°C) containing 100 IU penicillin-G and 100 μg streptomycin sulphate/ml. Oocytes were retrieved by follicle puncture technique from goat ovaries. Cumulus oocyte complexes (2132) were selected for in-vitro maturation, fertilization and culture. Oocytes were matured in TCM–199 medium (L-glutamin, sodium pyruvate, gentamycin sulphate and supplemented with 20% estrus goat serum at 38.5°C and 5% CO2 under humidified air for 27h. In-vitro matured oocytes (290) were denuded after 27h following culture by overtaxing, fixed for 15 min in 2.5% (w/v) glutaraldehyde, washed twice with PBS, stained with 0.1μg/ml 4,6–diamino– 2–phenylindol and mounted on slides. The evaluation of nuclear status was done by epifluorescence microscopy. After 27h of In-vitro maturation, oocytes (n=1447) were denuded and washed in sperm TALP and then fertilized in a drop of fertilization TALP (20% EGS and 10 μg/ml heparin) containing 1×106 spermatozoa/ml from Sirohi buck. Oocytes-sperm after 18h of co-incubation were washed in embryo development medium for 15–20 times. The cleaved embryos were randomly divided into 2 groups. Group 1 in-vitro fertilized oocytes (282) were co-cultured with oviductal epithelial cells in a 50μl drop of embryo development medium. In group 2 in-vitro fertilized oocytes (330) were cultured over a granulose cell monolayer in a 50μl drop of embryo development medium. Development of in-vitro fertilized oocytes were observed at every 24h till day 7 post insemination under inverted phase contrast microscope. The percentage of aberrations, GV, GVBD, MI and MII stage oocytes were 7.24, 4.82, 3.79, 14.82 and 61.37%, respectively. The percentage of 2–cell, 4–cell, 8–cell and morula were 47.87, 28.36, 14.89 & 8.86% and 65.45, 25.15, 6.36 and 3.03%, respectively, in groups 1 and 2. In conclusion, the present results indicate that (i) the granulosa cell monolayer significantly (P